The Influence Of Superstitious Beliefs And Magical Thinking On Generation Z's Purchasing Behavior In Indonesia - Heni Krisnatalia; Hendrajaya Hendrajaya; Idah Kusuma (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research is about delving into the fascinating world of Generation Z behavior, where superstition and mysterious thinking have taken on a real quality as a charming mental component. Superstitious beliefs and magical thinking, regularly formed in frivolity and common explanations, and enchanted thinking, characterized by a belief in strong causality, all influence customer choices. The aim of the research is to determine the influence of consumers' superstitious on their purchasing behavior. Furthermore, data was collected through a questionnaire in Google Forms format and a survey link was sent to consumers via the online communication media